Tear substitution therapy optimization of dry eye syndrome and cataract patients - S. N. Sakhnov; S. V. Yanchenko; A. V. Malyshev; A. R. Ceeva; L. M. Petrosyan; O. A. Baskakov; G. L. Kolomiec (Российский офтальмологический журнал)
Purpose: to evaluate the effectiveness of approaches to tear substitution in dry eye syndrome (DES) patients before cataract phacoemulsification (CPE). Material and methods. 60 DES and cataract patients who received preoperative therapy — tear substitute instillations (4 times a day, 1 month), were examined before CPE. They were divided into 2 groups each of which was subdivided into two subgroups. Group 1 included 30 mild DES patients with lipid deficiency who had a negative lipid interference test, meibomian gland dysfunction (MGD), and aqua deficiency absence (Schirmer-1 test > 15 mm). The subgroup 1.1 (15 patients) received 0.18 % sodium hyaluronate (SH) instillations (Gilan comfort), while the other subgroup 1.2 received “fat-water” type emulsion instillations. Group 2 consisted of 30 moderate DES patients with lipid-aqua deficiency, who also had negative lipid interference test, MGD, and aqua deficiency presence. Subgroup 2.1 (15 patients) received 0.3 % sodium hyaluronate (SH) instillations (Gilan ultra comfort), while subgroup 2.2 patients received “fat-water” type emulsion instillations. We evaluated: the OSDI points, and tear break-up time (TBUT). Results. As a result of therapy, a positive effect of the therapy on OSDI and TBUT was observed in all subgroups. In group 1 , OSDI decrease and TBUT increase were more pronounced in subgroup 1.1 patients, however, this difference between subgroups was not statistically significant. In group 2, OSDI decrease and TBUT increase were more pronounced and statistically significant in subgroup 2.1 patients. Conclusion. In patients with mild DES and lipid deficiency, 0.18 % SH (Gilan comfort) demonstrated a positive effect on OSDI and TBUT comparable to the “fat-water” type emulsion. In moderate DES patients with lipid-aqua deficiency, 0.3 % SH (Gilan ultra comfort) demonstrated a statistically significant and more pronounced positive effect on OSDI and TBUT than the “fat-water” type emulsion.